2021
DOI: 10.1111/joop.12364
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and resilience in first responders and health care workers during the COVID‐19 pandemic

Abstract: During the COVID-19 pandemic, first responders and health care workers faced elevated virus-related risks through prolonged contacts with the public. Research suggests that these workers already experienced lower levels of psychological well-being linked to occupational risks. Thus, the pandemic's impact might have particularly affected mental health in these groups. This paper analysed data from a large-scale Welsh population study (N = 12,989) from June to July 2020. Levels of psychological distress were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 36 publications
4
31
0
Order By: Relevance
“…Finally, it is worth mentioning that since publishing our initial report (1), much research continues to highlight the widespread negative impacts of the pandemic on mental health, 13). However, as was true at the time of our first report, the effects of this crisis have not been homogenous, with some positive changes also being noted (14)(15)(16)(17). In order to better make sense of this diversity of findings, future efforts may be directed at merging insights derived from populationlevel assessments with analysis of individual-centric subjective reports.…”
mentioning
confidence: 58%
“…Finally, it is worth mentioning that since publishing our initial report (1), much research continues to highlight the widespread negative impacts of the pandemic on mental health, 13). However, as was true at the time of our first report, the effects of this crisis have not been homogenous, with some positive changes also being noted (14)(15)(16)(17). In order to better make sense of this diversity of findings, future efforts may be directed at merging insights derived from populationlevel assessments with analysis of individual-centric subjective reports.…”
mentioning
confidence: 58%
“…Given its comprehensiveness, the PROSPER framework may be particularly relevant during the COVID-19 pandemic; for example, a recent investigation ( Lee et al, 2022 ) has demonstrated that a 4-session PROSPER-based psychological intervention program enhanced positive relationships with peers among pre-service teachers in Hong Kong during the COVID-19 pandemic. There is also research showing how its dimensions, such as positive emotions ( Coifman et al, 2021 ), relationships ( Hutchinson et al, 2021 ), perceived competence ( Behzadnia & FatahModares, 2020 ), resilience ( Pink et al, 2021 ), strengths ( Datu, Yuen, et al, 2022 ; Datu, Valdez, et al, 2022 ), engagement ( Ployhart et al, 2021 ), and meaning in life ( Newman et al, 2021 ), operate as either protective psychological resources or key psychological outcomes during the pandemic. Furthermore, the present research organized well-being outcomes into two broad categories, namely intrapersonal and interpersonal dimensions, given that previous literature ( Ryff, 1995 ) has offered a more nuanced approach in understanding the role of PWB's dimensions in different cultural contexts.…”
Section: Prosper Frameworkmentioning
confidence: 99%
“…They also provide a basis on which to recommend interventions based on both individual and team‐based factors in attempts to assist HSCWs in coping with stressors, both personal and systemic, rather than focusing on either factor alone. Growing evidence shows that reinforcing social bonds among colleagues, collaborative working and building effective and cohesive teams are highly protective factors in maintaining and improving staff well‐being (Aughterson et al, 2021 ; Cogan et al, 2022 ; Greenberg & Tracy, 2020 ; Khalili et al, 2021 ; Pink et al, 2021 ). Management and leadership initiatives in mental health services should be targeted at creating this combination within the working environment and prioritising staff well‐being.…”
Section: Discussionmentioning
confidence: 99%